IJCM_291A: Hygiene Practices Among Food Handlers in a Hospital Setting: A Case Study from District Hospital Parbhani - Surwase Kishor Kaluram; Doibale Mohan; Lakhmawar Nagesh (Wolters Kluwer Medknow Publications, 2024)
Background: The role of food handlers in maintaining food safety, especially in healthcare settings, cannot be overstated. Poor hygiene practices can lead to foodborne illnesses, which are particularly dangerous in a hospital environment where patients may have compromised immune systems. Ensuring high standards of personal hygiene among food handlers is crucial in healthcare settings to prevent foodborne illnesses. This study focuses on the hygiene practices of food handlers in a hospital environment. Objective: To assess the personal hygiene practices of food handlers in District Hospital Parbhani. The study aims to identify the adherence level to hygiene standards and pinpoint areas for potential improvement in food safety practices. Methodology: A cross-sectional survey was employed, targeting food handlers in District Hospital Parbhani. The survey utilized a structured questionnaire to collect data on various aspects of personal hygiene, including hand hygiene, personal cleanliness, and safe food handling methods. The participants were also interviewed to understand their knowledge and attitudes towards food safety. The data collected was then systematically an analysed to identify patterns, strengths, and areas needing improvement in the hygiene practices of the food handlers. Results: In our study at District Hospital Parbhani, among the 126 food handlers, a notable 45.24% were below 30 years of age. When assessing hygiene practices, 74% of the handlers had clean nails, and approximately 50% practiced hand washing with soap and water after using the toilet. The cleanliness of kitchen areas was maintained by 73% of the establishments, with 62% using soap and detergents for cleaning purposes. Conclusion: The study highlights the critical role of rigorous personal hygiene practices among food handlers in healthcare settings. It recommends ongoing training and periodic evaluations at District Hospital Parbhani to sustain and enhance these hygiene standards, thereby ensuring the health and safety of patients and staff.